THE EXTERNAL FUNCTION OF AUTOMOTIVE COMPANY PUBLIC RELATIONS IN BUILDING A POSITIVE IMAGE OF THE COMPANY (Analysis of Customer Relations Division of PT. Indomobil Trada Nasional / NISSAN in Serving Customers) - Putri Handayani; Eli Apud Saefudin; Meiby Zulfikar; Rizqi Fitrianti; Arfian Suryasuciramdhan; Luis Fiska Rahayu; Rizki Amilia (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
A company needs communication between companies with other companies and communication with its customers so that there is harmony and harmony and in order to create a good interaction for superiors, subordinates and customers, every company needs Public Relations which can mediate between the company and the consumers. One of the reasons for the existence and need for PR in a company is the presence of competitors and high innovation, one of which is in the automotive world. It is these competitors who make the presence of PR very necessary in fostering quality communication, both internally and externally. Of course the presence of PR must also provide fresh air for the company, not just communicating and establishing relationships, but how are the PR efforts and strategies in carrying out their functions. Providing excellent service and promotion is part of PR in communication. Competitors such as Toyota, Mazda, Mitsubishi, Honda, Kia, Mercy, Suzuki, and other automotive companies are of course increasingly paying attention to customer service, making people smarter in choosing vehicle brands (trade). This is the background of the existence of PR is very necessary in a company. One, the external function of PR is to create good excellent service, increase customer satisfaction, foster a sense of loyalty to return to buy products and enjoy the services provided and of course customers who are loyal to our products, will promote to those closest to them that the company's products and services better quality than other automotive companies. PT. Indomobil Trada Nasional (NISSAN) is present in the midst of society to accompany and serve consumers.